1997
DOI: 10.1099/00221287-143-1-109
|View full text |Cite
|
Sign up to set email alerts
|

The Plasmid-Located Haloalkane Dehalogenase Gene from Rhodococcus Rhodochrous NCIMB 13064

Abstract: The haloalkane dehalogenase (dhaA) gene from Rhodococcus rhodochrous NCIMB 13064 was cloned and sequenced. I t s comparison with the previously studied dhlA gene from Xanthobacter autotrophicus GJlO did not show homology. However, the amino acid sequences of the products of these genes showed approximately 30% identity and several of the catalytic amino acid residues were conserved in the NClMB 13064 dehalogenase. A high level of dhaA expression was demonstrated in Escherichia coli cells and this gene was show… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
91
0

Year Published

1997
1997
2017
2017

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 114 publications
(91 citation statements)
references
References 32 publications
0
91
0
Order By: Relevance
“…This highly toxic compound is degraded by the haloalkane dehalogenase (dhaA) gene product. A highly conserved dhaA gene was also found in phylogenetically distant Pseudomonas pavonaceae and Rhodococcus rhodochrous (Kulakova et al, 1997), organisms isolated, like Mycobacterium sp. strain GP1, from different strongly contaminated environmental samples.…”
Section: Resultsmentioning
confidence: 87%
See 1 more Smart Citation
“…This highly toxic compound is degraded by the haloalkane dehalogenase (dhaA) gene product. A highly conserved dhaA gene was also found in phylogenetically distant Pseudomonas pavonaceae and Rhodococcus rhodochrous (Kulakova et al, 1997), organisms isolated, like Mycobacterium sp. strain GP1, from different strongly contaminated environmental samples.…”
Section: Resultsmentioning
confidence: 87%
“…strain GP1, from different strongly contaminated environmental samples. Remarkably, in Rhodococcus rhodochrous the dhA region was located on the autotransmissible plasmid pRTL1 (Kulakova et al, 1997). Another case of potentially recent HGT was suggested by the sequence analysis of the linear plasmid pCLP from Mycobacterium celatum, which revealed loci with high nucleotide sequence identity to loci on the M. tuberculosis chromosome (Le Dantec et al, 2001).…”
Section: Resultsmentioning
confidence: 99%
“…Moraxella B (DehH1, Genbank/EMBL Accession Number D90422; Kawasaki et al, 1992), tetrachlorocyclohexadiene dehalogenase from Sphingomonas paucimobilis (LinB, D14594; Nagata et al, 1993), and 1-chloroalkane halidohydrolase from Rhodococcus rhodochrous NCIMB13064 (DhaA, L49435; Kulakova et al, 1997) showed that they have considerable homology with DhlA (M26950), suggesting FIGURE 2: Sequence alignment of haloalkane dehalogenase from Xanthobacter autotrophicus GJ10 (DhlA; Janssen et al, 1989), haloacid dehalogenase from Moraxella B (DehH1; Kawasaki et al, 1992), tetrachlorocyclohexadiene dehalogenase from Sphingomonas paucimobilis (LinB; Nagata et al, 1993), and 1-chloroalkane halidohydrolase from Rhodococcus rhodochrous NCIMB13064 (DhaA; Kulakova et al, 1997). The sequence comparison was carried out using the program DNASTAR (DNASTAR Inc., Madison, WI).…”
Section: Sequence Alignment Of R/ -Hydrolase Fold Dehalogenases Sequmentioning
confidence: 99%
“…tub., gene products from M. tuberculosis H37Rv encoded by the adhD and adhB genes, respectively, which have been assigned as putative alcohol dehydrogenases by Cole et al (1998) ; hyp-ADH R. rho., gene product from R. rhodochrous, whose corresponding gene is found in a plasmid-located operon related to haloalkane dehalogenation, which has been assigned as a hypothetical alcohol dehydrogenase by Kulakova et al (1997). Data from Eklund et al (1990) for the corresponding residues of NAD-dependent alcohol dehydrogenase from horse liver (the ethanol-active subunit : E-type) are included for comparison.…”
Section: Discussionmentioning
confidence: 99%
“…1. Also, a significant sequence identity (51 %) was observed with a hypothetical alcohol dehydrogenase from R. rhodochrous NCIMB 13064, whose corresponding gene occurs in a dehalogenation operon (Kulakova et al, 1997), and with the AdhB gene product (46 %) from M. tuberculosis (not shown). Recently, the complete amino acid sequence of np-ADH from A. methanolica has been determined and structural modelling was carried out using this sequence and the known three-dimensional structure of horse liver alcohol dehydrogenase (see Piersma, 1998).…”
Section: Residuementioning
confidence: 99%